A estimulação cognitiva em trabalhadores idosos: possíveis impactos desta intervenção - Longhi, Claire (My University, 2022)
The changes in the age pyramid, which have happened due to the decrease in fertility rate and the increase in life expectancy, have been generating a significant rise in the percentage of people who are 60 years of age or older. This aging process will most certainly strain elderly people on taking part in regular social activities, mainly in the labor market. The Active Aging Policy, developed in 2005 by the World Health Organization, defines four pillars: "health", the "right to security", "the participation of the elderly in society" and "lifelong learning". These pillars formulate actions for healthy and active aging, the improvement of quality of life and lifelong learning that help to postpone the onset of cognitive declines that result in difficulties in old age. Therefore, the research problem that made this investigation was how cognitive stimulation interventions can impact the cognitive and productive performance of older workers in the work environment. The theoretical basis was made from the authors Baltes, with their proposal from the lifespan perspective, and Bernal. The main objective of this dissertation is to analyze how cognitive stimulation interventions can impact the cognitive development of elderly workers in the work environment. The specific objectives are: a) to identify the cognitive and productive level before and after interventions; b) describe the workers' perceptions about the possible impacts of the cognitive stimulation strategies carried out; c) to know possible changes in the strategies used by elderly workers to learn nowadays; d) knowing possible impacts on the productive performance of elderly workers in the work environment; and e) offer theoretical support for the proposition of cognitive stimulation exercises focused on professional and personal performance. The methodology is characterized by having a descriptive research with a mixed approach, contemplating qualitative and quantitative aspects. The sample was intentionally constituted and composed of eight elderly workers, five women and three men from a food industry in the city of Nova Petrópolis/RS. The quantitative approach used the application of a cognitive screening instrument (MoCa) and a job satisfaction investigation instrument (EST), which were analyzed with the Jomovi and Jasp data analysis software. The qualitative approach was carried out based on Content Analysis, proposed by Bardin, and they were organized into two categories: "Possibilities for learning in the work environment beyond work" and "Learning strategies". The analysis of the results showed that age as an isolated factor isn't a determinant of cognitive decline. There was also no correlation between the participants' education and their performance. The results of the investigation of job satisfaction did not identify dissatisfaction in any of the analyzed dimensions, and the dimensions of "satisfaction with colleagues", "satisfaction with the boss" and "satisfaction with the nature of work" showed that participants are satisfied , and the dimensions of "satisfaction with salary" and "satisfaction with promotions" indicated indifference. The reassessment of participants with the cognitive screening test, after the cognitive stimulation sessions, showed a significant positive evolution between the first and second assessment: p = 0.011. In an individual analysis of the cognitive domains, it was found that the domains of "language" and "delayed recall" present scores with a significantly higher difference after the application of stimulation sessions: p = 0.036 and p = 0.010, respectively. The "naming" and "abstraction" domains, despite not presenting results within the significance parameters, had results very close to this, with p = 0.074 and p = 0.087, respectively. Finally, the results of the "visual-spatial/executive functions" (p = 0.293), "attention" (p = 1) and "orientation" (p = 0.977) domains did not show significant evolution after the second assessment. The results presented in these last three domains can be explained, in part, by the maximum performance of the participants in the first test performed, thus preventing any possible improvement in performance from being observed in the second evaluation of the cognitive screening test. The qualitative questionnaire showed an improvement in the participants' quality of life, both personally and professionally. The appropriation of new learning styles experienced in the stimulation sessions along with the integration with others have impacted the participants positively. That said, the main conclusions from this study based on the outcomes found are that, in general, there is efficiency in the practice of cognitive stimulation as a tool to improve the participants' cognitive performance and in the development of better quality of life. This study, therefore, serves as a reference for the use of cognitive stimulation as a tool to promote health and quality of life in aging, in order to delay the manifestation of cognitive decline. [resumo fornecido pelo autor]
A modificação da pirâmide populacional, decorrente da redução da taxa de fecundidade e do aumento da expectativa de vida, está produzindo um acréscimo significativo na proporção da população com 60 anos ou mais. Este envelhecimento tensionará a participação dos velhos na sociedade, principalmente no mercado de trabalho. A Política do Envelhecimento Ativo, desenvolvida em 2005 pela Organização Mundial da Saúde, define quatro pilares: a "saúde", o "direito à segurança", a "participação dos idosos na sociedade" e a "aprendizagem ao longo da vida". Estes pilares formulam ações visando um envelhecimento saudável e ativo, a melhoria da qualidade de vida e a aprendizagem ao longo da vida que auxiliam a postergar o aparecimento de declínios cognitivos que resultem em dificuldades na velhice. Neste sentido, o problema de pesquisa que desencadeou esta investigação foi como intervenções de estimulação cognitiva podem impactar no desempenho cognitivo e produtivo de trabalhadores idosos no ambiente de trabalho. O embasamento teórico foi realizado a partir dos autores Baltes, com sua proposta da perspectiva lifespan, e Bernal. Esta dissertação possui como objetivo principal analisar como intervenções de estimulação cognitiva podem impactar no desenvolvimento cognitivo de trabalhadores idosos no ambiente de trabalho. Para dar conta deste, são objetivos específicos: a) identificar o nível cognitivo e produtivo pré e pós intervenções; b) descrever as percepções dos trabalhadores sobre possíveis impactos das estratégias de estimulação cognitiva realizadas; c) conhecer possíveis mudanças nas estratégias utilizadas pelos trabalhadores idosos para aprenderem atualmente; d) conhecer possíveis impactos no desempenho produtivo dos trabalhadores idosos no ambiente de trabalho; e e) oferecer subsídios teóricos para a proposição de exercícios de estimulação cognitiva com foco no desempenho profissional e pessoal. A metodologia caracteriza-se por ter uma pesquisa descritiva de abordagem mista, contemplando aspectos qualitativos e quantitativos. A amostra foi constituída de forma intencional e composta por oito trabalhadores idosos, sendo cinco mulheres e três homens de uma indústria de alimentos da cidade de Nova Petrópolis/RS. A abordagem quantitativa do campo utilizou a aplicação de um instrumento de rastreio cognitivo (MoCa) e de um instrumento de investigação de satisfação no trabalho (EST), que foram analisados com os softwares de análise de dados Jomovi e Jasp. A abordagem qualitativa foi realizada a partir da Análise de Conteúdo, proposta por Bardin, e foram organizadas em duas categorias: "Possibilidades de aprendizagem no ambiente de trabalho para além da atividade laboral" e "Estratégias de aprendizagem". A análise dos resultados na pesquisa demonstrou que a idade como fator isolado não é determinante do declínio cognitivo. Também não se identificou correlação entre a escolaridade dos participantes e seu desempenho. Os resultados da investigação da satisfação no trabalho não identificaram insatisfação em nenhuma das dimensões analisadas, sendo que as dimensões de "satisfação com os colegas", "satisfação com a chefia" e "satisfação com a natureza do trabalho" mostraram que os participantes, no geral, estão satisfeitos, e as dimensões de "satisfação com o salário" e "satisfação com as promoções" indicaram indiferença. A reavaliação dos participantes com o teste de rastreio cognitivo, após as sessões de estimulação cognitiva, demonstrou uma evolução positiva significativa entre a primeira e segunda avaliação: p = 0,011. Em análise individualizada dos domínios cognitivos, constatou-se que os domínios de "linguagem" e "evocação tardia" apresentam pontuação com diferença significativa maior após a aplicação das sessões de estimulação: p = 0,036 e p = 0,010, respectivamente. Os domínios de "nomeação" e "abstração", apesar de não apresentarem resultados dentro dos parâmetros significância, tiveram resultados muito próximos deste, com p = 0,074 e p = 0,087, respectivamente. Por fim, os resultados dos domínios "visuoespacial/funções executivas" (p = 0,293), "atenção" (p = 1) e "orientação" (p = 0.977) não demonstraram evolução significativa após a segunda avaliação. Os resultados apresentados nestes últimos três domínios podem ser explicados, em parte, pelo desempenho máximo dos participantes no primeiro teste realizado, impedindo, desta forma, que eventual melhora no desempenho pudesse ser observada na segunda avaliação do teste de rastreio cognitivo. O questionário qualitativo demonstrou melhora na qualidade de vida dos participantes, tanto em âmbito pessoal quanto profissional. A apropriação de novas estratégias de aprendizagem vivenciadas nas sessões de estimulação e a integração com o outro impactaram positivamente os participantes. Diante disso, as principais conclusões deste estudo baseadas nos resultados encontrados são de que, no geral, há eficácia da prática de estimulação cognitiva como instrumento de melhora no desempenho cognitivo dos participantes e na melhoria da qualidade de vida. Este estudo, portanto, serve como referência para utilização da estimulação cognitiva como ferramenta de promoção da saúde e qualidade de vida, no envelhecer, de maneira as postergar a manifestação de declínios cognitivos. [resumo fornecido pelo autor]
Keywords: Cognição em idosos; Trabalhadores idosos; Envelhecimento - Aspectos psicológicos; Qualidade de vida; Cognition in old age; Older people - Employment; Aging - Psychological aspects; Quality of life